RNA-seq reveals the role of miR-199a-3p in regulating inflammation of bovine mammary epithelial cells. (31st December 2022) - Li, Yu-Hang; Ren, Qian-Qian; Wang, Jin-Peng; Wang, Xing-Ping; Luoreng, Zhuo-Ma; Ma, Yun; Wei, Da-Wei
Abstract: MicroRNAs (miRNAs) are involved in the regulation of a variety of biological processes. However, the research on the regulatory role of bovine mammary epithelial cells (bMECs) is scarce. To date, there are no reports about the role of miR-199a-3p in bMECs. In this study, RNA sequencing (RNA-seq) technology was used to detect the transcriptomes of the miR-199a-3p overexpression and negative control (NC) groups of bMECs. Then, the screening and functional annotation of differentially expressed genes (DEGs) were conducted. The results showed that there were 140 DEGs (109 up-regulated and 31 down-regulated) in the miR-199a-3p overexpression group. The results of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that the DEGs might regulate the immune and inflammatory responses via the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway, transforming growth factor-beta (TGF-β) signaling pathway, and interleukin-17 (IL-17) signaling pathway, which revealed that miR-199a-3p might participate in regulating bMECs inflammation via affecting the expression of related genes and the above signaling pathways. This study may provide a new reference for potential therapeutic targets of cow mastitis. Highlights: Differential expression profiles of overexpressed miR-199a-3p were detected in bMECs. There were 140 DEGs in the miR-199a-3p overexpression group. DEGs were involved in bMECs inflammation by regulating related signaling pathways.